Ensaios sobre atividade economica, meio ambiente e saúde - Sousa, Wesley Leitão de (2022)
This thesis is composed of three essays on economy, environment and health. The first of the articles discusses the causes related to the occurrence of hotspots in South America based on annual data from 10 countries, between 2002 and 2018. To this end, an extensive literature review of empirical works in this area was carried out in order to elaborate a comprehensive model, containing several variables considered relevant. The estimations, carried out via negative binomial model, revealed that the relationship between hotspots and Gross Domestic Product per capita or hotspots and Human Development Index takes the form of "U-normal", that is, these indicators can accelerate the activity of hotspots in the South American region. To make the situation worse, forest cover, population density and unemployment induce fire activity in South America and in the Amazonian countries. From these results, public policies are suggested to combat and reduce hotspots in the South American continent. The second essay investigates the relationship between socioeconomic development and deforestation of Atlantic Forest remnants in the state of Ceará, using the Environmental Kuznets Curve (EKC) approach combined with the tobit model. To this end, the analysis in the period from 2011 to 2017 considered the GDPpc and controlled for factors associated with both deforestation and environmental protection. As a result, an“N”shaped curve was obtained between economic development and deforestation, suggesting that this form of environmental degradation is a cyclical phenomenon in the region. In addition, it was identified that 91.8% of the sampled municipalities are below the maximum point, a point that leads to environmental concerns, given that economic development can drive deforestation in the region. In this way, it is not guaranteed that the economic activity alone guarantees the environmental protection and sustainable use of the Atlantic Forest and associated ecosystems in the state of Ceará. The third and last one carries out an impact assessment of the infrastructure of thermoelectric plants I and II located in the Industrial and Port Complex of Pecém on hospital admissions and deaths in the municipalities of Caucaia and São Gonçalo do Amarante (SGA), in the state of Ceará. Using the synthetic control model in the period from 2001 to 2019, the results showed the average positive effect of the intervention on deaths per residence in the following analyzed units, the Caucaia/SGA Aggregate (21.83% per year) and Caucaia (23.80% per year). In addition, deaths are distributed by general causes, diseases in the circulatory and respiratory systems, among men, women and in the population over 60 years of age or not. In the municipality of SGA, no significant effects were observed, although unexpected, this result needs to be evaluated with caution, as there are limitations regarding the scope of this study. The research contributes to the theoretical literature that investigates the negative externalities arising from the infrastructure of the complex, as well as provides an agenda for new studies that assess the loss of human capital in the region.